Evaluation of Beam Forming Capability of Linear Antenna Array for Smart Antenna System - et. al., Sarmistha Satrusallya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increase in the number of users in a cellular network decreases the efficiency of the service provider. Array antenna improves the coverage, capacity and transmission quality of the system. Smart antenna system with digital signal processor has the capability to attain the gain and beam width for linear array in a desired direction. In this work, we analyze and compare linear arrays with 50 and 100 elements with different element spacing to achieve a narrow beam width. It was found that the spacing between the elements with number of elements is essential in determining the gain and First Null Beam Width (FNBW). For 50 numbers of element the gain is obtained as 17.3dB for a spacing 0.75λ and for 100 elements the gain is 20.38dB for a range of 0.6λ to0.75λ.